Hypogalactia as a cause of neonatal hypernatremia - A. P. Khokhlova; K. S. Zizyukina; H. A. Sarkisyan; Yu. V. Zhirkova; O. В. Kovalev; D. M. Muscherova; V. A. Mironova; A. A. Komarova; L. M. Makarova; N. V. Kholodnova; P. V. Shumilov (LLC "Diagnostics and Vaccines", 2024)
Neonatal hypernatremia is a condition in which the concentration of sodium in the blood of a newborn child exceeds 145 mmol/l. The causes of this pathology may be kidney disease, endocrine problems, transdermal water loss, iatrogenic sodium overload. In addition, dehydration due to insufficient breastfeeding remains one of the important factors leading to hypernatremia. Clinical signs include: significant weight loss, decreased skin turgor, anxiety, fever, seizures, and direct hyperbilirubinemia. The main complications of this condition are intracranial hemorrhages, venous sinus thrombosis and acute renal tubule necrosis. Infusion therapy and adequate oral nutrition are used to correct hypernatremia. The article presents a clinical case of hypernatremia in a newborn child caused by hypogalactyly in the mother. The purpose of the demonstration is to raise awareness and alertness among pediatricians and neonatologists about the possibility of this problem.